시력장애와 사지마비를 호소하는 시신경척수염 환자의 한방 증례 보고 1례 - 우성진; 신재욱; 장우석; 백경민; Woo, Seong-jin; Shin, Jae-wook; Jang, Woo-seok; Baek, Kyung-min (대한한방내과학회지, 2017)
Objectives: This is a case report regarding the effect of Korean traditional medicine on vision disorder and quadriplegia in a patient with neuromyelitis optica. Methods: We treated a patient who was diagnosed with neuromyelitis optica with Korean traditional medicine, including acupuncture, moxibustion, and herbal medicine (Gigugyanghyeol-tang gamibang) for 106 days. We evaluated the patient with the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI), Modified Barthel Index (MBI), Modified Ashworth Scale (MAS) Grade, and Numeric Rating Scale-11 (NRS-11). Results: After treatment, the patient's symptoms were improved. The ISNCSCI scores increased from 42 to 66 in motor score, from 152 to 196 in sensory score, and from A to D in the ASIA impairment scale; the MBI score increased from 9 to 33, while the score of the MAS Grade decreased from I+ to I, and the NRS-11 scores of vision disorder, spasticity, and tingling decreased from 10 to 7, 3, and 2-3, respectively. Conclusions: Korean traditional medicine may be effective for treatment of vision disorder and quadriplegia in patients with neuromyelitis optica.